Knowledge, Attitude And Practice Of Hypercholesterolemic Type 2 Diabetic Subjects On Dyslipidemia - Saleh, Farzana; Mumu, Shirin Jahan; Afnan, Fadia; Ali, Liaquat; Chaudhury, Habib Sadat; Akhter, Afroza; Ahmed, Kazi Rumana; Akter, Sanzida (Ibrahim Medical College Journal, 2012)
This study was undertaken to assess the knowledge, attitude and practice (KAP) of hypercholesterolemic type 2 diabetic subjects on dyslipidemia and to analyze the influence of some demographic and socioeconomic factors on the level of KAP.It was a descriptive cross-sectional survey. One hundred eleven newly diagnosed type 2 diabetic subjects (male 61%, female 39%, age 45±9 years, BMI 24±4.8 Kg/m2) with hypercholesterolemia (fasting plasma total cholesterol >200 mg/dl) were selected from the out patient department of BIRDEM by purposive sampling method. Data were collected by a pre-designed, pretested, interviewer-administered questionnaire. Three categories were defined on the basis of the score obtained by each subject namely low, medium and high as follows: knowledge-score <50%, 50-60% and >60%; attitude-score <60%, 60-80% and >80%; and practice-score <50%, 50-70% and >70% respectively. The levels of knowledge were low in 42%, medium in 35% and high in 23% of the study subjects. The corresponding attitude levels were low in 1%, medium in 31% and high in 68%, and the levels of practice were low in 80%, medium in 14% and high in 6% of the subjects. The knowledge score was higher in secondary and graduate (53.4±8.9%, and 54.9±10.1%) groups compared to illiterate-primary group (48.9±9.9%). Practice score of illiterate-primary group (34.5±16.8%) was lower than secondary and graduate (43.1±13.9% and 46.7±18.1%) groups, but they did not differ on attitude. The various income groups did not differ on knowledge. Attitude score of high-income group (78.7±8.4%) was better than low-income group (70.9±11.8%). Practice score in high-income group (44.7±16.0%) was better than medium income and low-income groups (31.3±14.5% and 28.6±15.0%). Knowledge and practice score in Bangladeshi hypercholesterolemic type 2 diabetic subjects are not satisfactory although they have fairly good attitude levels. Education and income status are the major determinants of knowledge, attitude and practice regarding dyslipidemia in diabetes. A coordinated policy is required to promote knowledge and attitude on healthy lifestyle and to translate those into practice. DOI: http://dx.doi.org/10.3329/imcj.v5i2.10096 IMCJ 2011; 5(2): 37-41